Integrasi Nilai-Nilai Manajemen (Ajennangeng) dalam Naskah Lontara Latoa Tana Bone: Sebuah Pendekatan Teori Manajemen - L., Idrus; Dwiyama, Fajri; R, Nurhasanah (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
"Integration of Management Values (Ajennangeng) in the Lontara Latoa Tana Bone Manuscript: A Management Theory Approach" aims to explore how the management values contained in the Lontara Latoa Tana Bone Manuscript can be integrated into modern management practices. This study uses a qualitative approach with descriptive analysis to understand the meaning and relevance of Ajennangeng's values in the current management context. The results of the study show that the values such as ethics, social responsibility, and collaboration contained in the Lontara Manuscript can serve as a guideline in more transparent and accountable managerial decision-making. In addition, this study also found that the integration of local values can increase stakeholder trust and strengthen people's cultural identity. Thus, this study recommends that a multidisciplinary approach that combines aspects of management, sociology, and anthropology can be adopted to better understand how management values (Ajennangeng) in the lontara Latoa Tana Bone manuscript can be integrated in a broader context.